2012
DOI: 10.1016/j.molcel.2011.11.022
|View full text |Cite|
|
Sign up to set email alerts
|

Importin 7 and Exportin 1 Link c-Myc and p53 to Regulation of Ribosomal Biogenesis

Abstract: Summary Members of the β-karyopherin family mediate nuclear import of ribosomal proteins and export of ribosomal subunits, required for ribosome biogenesis. We report that transcription of the β-karyopherin genes importin 7 (IPO7) and exportin 1 (XPO1), and several additional nuclear import receptors, is regulated positively by c-Myc and negatively by p53. Partial IPO7 depletion triggers p53 activation and p53-dependent growth arrest. Activation of p53 by IPO7 knockdown has distinct features of ribosomal bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 84 publications
5
100
0
2
Order By: Relevance
“…S7A). To provide further support for this finding, we compared the dynamics of nucleoar recovery of YFP-L11 between untreated and ActD-treated H1299 cells by using fluorescence recovery after photobleaching (7,27,30). In the presence of ActD, we observed a significant recovery of fluorescent YFP-L11 in the nucleoli after photobleaching.…”
Section: Accumulation Of Ribosome-free L5 and L11 Is Due To Their Mutualmentioning
confidence: 73%
See 1 more Smart Citation
“…S7A). To provide further support for this finding, we compared the dynamics of nucleoar recovery of YFP-L11 between untreated and ActD-treated H1299 cells by using fluorescence recovery after photobleaching (7,27,30). In the presence of ActD, we observed a significant recovery of fluorescent YFP-L11 in the nucleoli after photobleaching.…”
Section: Accumulation Of Ribosome-free L5 and L11 Is Due To Their Mutualmentioning
confidence: 73%
“…In cancers retaining wild-type p53, the functions of p53 are likely inactivated by defects in its upstream regulators and downstream targets. Although DNA damage is common to most p53-activating stresses, evidence accumulated over the last decade suggests that perturbation of ribosome biogenesis triggers a p53-activating signaling pathway independently of DNA damage (2,(4)(5)(6)(7). It was originally suggested that this pathway has a prominent role in preventing diseases by monitoring the fidelity of ribosome biogenesis (4).…”
mentioning
confidence: 99%
“…After additional 24 h, cells were analyzed for BrdU incorporation as previously described. 30,31 Colony-formation assays. Twenty-four hours after seeding, cultures were transfected with 20 nM miR-661 or miR-C. After additional 24 h, cells were counted, seeded in a six-well plate at a density of 3000 cells/well and incubated for 8 days at 37 1C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Myc uniquely activates genes driven by RNA polymerases I and III, which are required for the expression of ribosomal RNAs (Gomez-Roman et al 2006). Intriguingly, Myc stimulates and p53 opposes the expression of importin 7 (IPO7), which regulates the import of specific ribosomal proteins for ribosomal assembly, suggesting that cellular stresses regulate ribosome biogenesis through p53 (Golomb et al 2012). In fact, Mdm2 senses nucleolar imbalance in ribosome biogenesis via binding of excess RPL11 and RPL5 with Mdm2, resulting in elevated p53 (Deisenroth and Zhang 2011).…”
Section: Growth Factor-stimulated Transcriptional Responsesmentioning
confidence: 99%